Property rights : a re-examination - Penner, J. E. (James E.) (Oxford : Oxford University Press, 2020)
Ranging over a host of issues, Property Rights: A Re-Examination pinpoints and addresses a number of theoretical problems at the heart of property theory. Part 1 reconsiders and refutes the bundle of rights picture of property and the related nominalist theories of property; Part 2 explores in detail the Hohfeldian theory of jural relations; Part 3 considers the form and justification of property rights, beginning with the relation an owner's liberty to use her property and her 'right to exclude', with particular reference to the tort of nuisance, anb concludes by addressing the ever-vexed question of property rights in land.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Right of property; Right of property -- Philosophy; Law; Laws of specific jurisdictions & specific areas of law